Child Marriage Dispensation and the Paradox of Legal Protection: A Normative Analysis of Judges' Legal Reasoning - Sri Atika; Iksan; Zuhrah (CV. Creative Tugu Pena, 2026)
This article examines the practice of child marriage dispensation within the Indonesian marriage law system by highlighting the paradox of legal protection embedded in judicial reasoning. Following the reform of the minimum marriage age under Law Number 16 of 2019, the study aims to analyze whether the dispensation mechanism is applied consistently with the objective of child protection. Employing a normative legal research approach, this study analyzes statutory regulations, child protection principles, and the structure of judicial reasoning in court decisions granting child marriage dispensation. The findings reveal that although child protection is normatively acknowledged, judicial practice tends to prioritize short-term pragmatic and social considerations, thereby weakening the preventive function of the minimum marriage age norm. Judicial reasoning frequently normalizes dispensation as an expedient solution, resulting in a shift from substantive child protection to a formal-procedural approach. This article concludes that strengthening child protection in child marriage dispensation cases requires a reorientation of judicial reasoning that consistently places the best interests of the child as the primary evaluative standard and substantive objective in judicial decision-making